Analysis of spatial appropriateness, green spaces, accessibility and enclosed residential towns on the performance component of the quality of environment with fuzzy logic approach (case study: district 6 in region 5 of Tehran) - shahin khalilian; fariba Alborzi; jamalaladin sohili (تحقیقات کاربردی علوم جغرافیایی)
. The research method used in this research is descriptive-analytical, survey and quasi-experimental of simulation kind. Data from research samples with survey method and other data were obtained using written sources and documentary studies and collection tool was selected according to the research objectives based on GIS maps and AutoCAD software outputs and simulation tools or the modeling in Revit software and then were investigated in Excel and the analysis of appropriateness was carried out with the help of simulated outputs and two-dimensional and three-dimensional maps and, a fuzzy logic method was used in MATLAB software, and the sample population is extracted based on a stratified sampling method and the selected residential settlements were in the sixth district of region 5 of Tehran and these residential settlements including Apadana, Ekbatan Phase II and Ekbatan Phase I and III. This article was analyzed with the aim of identifying the role of open and enclosed spaces for residential complexes on improving the quality of the environment, including efficiency by using field multi-criteria fuzzy logic method. After analyzing the data, the results of studying the spatial ratios in three samples of residential area in Tehran's 5th district with the performance component of the quality of the environment show that by decreasing the mass ratio (indoor spaces) and increasing the ratio of space (access spaces and green), increasing the quality of the environment cannot be reached, but also increasing the quality of the environment is in direct contact with the observing the proportionality component of the space between the mass and space proportions